2021
DOI: 10.3390/nano11030736
|View full text |Cite
|
Sign up to set email alerts
|

HKUST-1@IL-Li Solid-state Electrolyte with 3D Ionic Channels and Enhanced Fast Li+ Transport for Lithium Metal Batteries at High Temperature

Abstract: The challenge of safety problems in lithium batteries caused by conventional electrolytes at high temperatures is addressed in this study. A novel solid electrolyte (HKUST-1@IL-Li) was fabricated by immobilizing ionic liquid ([EMIM][TFSI]) in the nanopores of a HKUST-1 metal–organic framework. 3D angstrom-level ionic channels of the metal–organic framework (MOF) host were used to restrict electrolyte anions and acted as “highways” for fast Li+ transport. In addition, lower interfacial resistance between HKUST-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 79 publications
0
12
0
Order By: Relevance
“…Li et al utilized a Li-[EMIM][TFSI]@HKUST-1 SSE for the development of fast lithium ion transport in LIBs at elevated temperatures [ 97 ]. This SSE has a high thermal stability (up to 300 °C) with a relatively good ionic conductivity and Li + transference number of 0.68 × 10 −4 S cm −1 and 0.46 at 25 °C, respectively.…”
Section: Ionic Liquid@metal–organic Framework (Il@mof) As a Solid-sta...mentioning
confidence: 99%
“…Li et al utilized a Li-[EMIM][TFSI]@HKUST-1 SSE for the development of fast lithium ion transport in LIBs at elevated temperatures [ 97 ]. This SSE has a high thermal stability (up to 300 °C) with a relatively good ionic conductivity and Li + transference number of 0.68 × 10 −4 S cm −1 and 0.46 at 25 °C, respectively.…”
Section: Ionic Liquid@metal–organic Framework (Il@mof) As a Solid-sta...mentioning
confidence: 99%
“…Based on the above studies, it can be concluded that the pore size of MOFs is one of the key factors in the encapsulation of ILs. The pore diameters of the MOFs mentioned above are as follows: UIO-67, tetrahedral and octahedral cages with diameters of 12 Å and 16 Å; UIO-66, tetrahedral and octahedral cages with diameters of 7.5 Å and 12 Å; HKUST-1, 74 pore diameter of about 8 Å; MOF-525(Cu), an aperture size of 12 × 7 Å, while the size of the cation and anion in the ionic liquid is [EMIM] + (7.6 × 4.3 Å) and [TFSI] − (7.9 × 2.9 Å). Obviously, UIO-67 has the largest pore size, thus the restriction effect on the IL is not obvious and has the lowest ion migration number.…”
Section: Mofs As Solid-state Electrolytes For Li-metal Batteriesmentioning
confidence: 99%
“…In the first cycle, a high irreversible capacity is observed, which is related to the formation of the solid electrolyte interface (SEI), but from the second cycle on, the capacity is practically constant, providing a reversible discharge capacity of 3,000 mAh g −1 at 0.1C. Cu (HKUST-1) ( Dutta and Kumar, 2019 ; Li et al, 2021 ), Cr (MIL-101) ( Xu et al, 2019 ) and Al (MIL-121) based MOFs ( Zettl and Hanzu, 2021 ) have also been studied as ionic conductors.…”
Section: Implementation Of Il@mof Hybrid Solid Electrolytes In LI And...mentioning
confidence: 99%